Subchorionic Hematomas and Adverse Pregnancy Outcomes among Twin Pregnancies - Naqvi, Mariam; Naert, Mackenzie N.; Khadraoui, Hanaa; Rodriguez, Alberto M.; Namath, Amalia G.; Ali, Munira; Fox, Nathan S. (American Journal of Perinatology, 2019)
Objective This study estimates the association of a first trimester finding of subchorionic hematoma (SCH) with third trimester adverse pregnancy outcomes in women with twin pregnancies.Study Design Retrospective cohort study of twin pregnancies prior to 14 weeks at a single institution from 2005 to 2019, all of whom had a first trimester ultrasound. We excluded monoamniotic twins, fetal anomalies, history of fetal reduction or spontaneous reduction, and twin-to-twin transfusion syndrome. Ultrasound data were reviewed, and we compared pregnancy outcomes after 24 weeks in women with and without a SCH at their initial ultrasound 60/7 to 136/7 weeks. Regression analysis was used to control for any differences in baseline characteristics.Results A total of 760 women with twin pregnancies met inclusion criteria for the study, 68 (8.9%) of whom had a SCH. Women with SCH were more likely to have vaginal bleeding and had their initial ultrasound at earlier gestational ages. On univariate analysis, SCH was not significantly associated with gestational age at delivery, preterm birth, birthweight of either twin, low birthweight percentiles of either twin, fetal demise, or preeclampsia. SCH was associated with placental abruption on univariate analysis, but not after controlling for vaginal bleeding and gestational age at the time of the initial ultrasound (adjusted odds ratio: 2.00, 95% confidence interval: 0.63–6.42). Among women with SCH, SCH size was not associated with adverse pregnancy outcomes.Conclusion In women with twin pregnancies, the finding of a first trimester SCH is not associated with adverse pregnancy outcomes >24 weeks.
Keywords: twin; subchorionic hematoma; first trimester; adverse outcome